23 Creatine supplementation and swimming performance; a systematic review and meta-analysis. (13th October 2015) - Morgan, C; Johnston, A; Sansome, S
Abstract : Creatine as an ergogenic aid in sport has been an area of significant scientific research. Creatine supplementation should theoretically increase total muscle creatine and enhance the generation of intramuscular phosphocreatine and subsequent ATP formation. However the effect of creatine supplementation on swimming performance has received little attention. In swimming creatine could help maintain maximal power output, aid recovery and increase lean body mass. A literature review was conducted to identify the evidence that creatine supplementation alters swimming performance. Twenty-seven potential studies were identified, seventeen were selected for review. The studies were then categorised as swimming a short distance race (single sprint performance), or swimming a series of sprints with intervals of rest (repeated interval performance). None of the studies controlled for the multiple confounding factors associated with measurement of swimming performance. The sample size was limited, reducing the reliability of the studies and introducing the possibility of bias. The studies provided insufficient evidence to determine if creatine supplementation was beneficial. However, what data there was supported the use of creatine supplementation in repeated interval swimming rather than single sprint. From a review of the studies, it was calculated, there was a 1.5% increase in swimming performance with the use of creatine for repeated intervals and a 0.8% increase in performance for single sprint. While this may seem minor, it should be remembered swimming races are often won by much smaller margins. In the 2012 Olympics the Men's 100 metres freestyle race was won by a margin of 0.01 of a second (0.02%). Thus even this small improvement could make a difference to the final outcome of the race.